A prospective study to evaluate functional results of PHILOS locking plate system in management of proximal humerus fractures in adults - Gawali, Satish R.; Sonkawade, Venktesh D.; Nair, Pradeepkumar S.; Mate, Gaurav B. (International Journal of Research in Orthopaedics, 2021)
Background: Various management options are available for management of proximal humerus fractures where PHILOS plating is one of them. But data available in literature on its use and efficacy in management of all types of proximal humerus fractures is still dicey. So, we through our study attempted to grow our knowledge regarding its functional results, complication rates, etc. for use in coming future. Methods: 30 patients with proximal humerus fractures classified on the basis of Neer’s classification were included in study who were operated from 2018 to 2020 at our institute. These patients were operated by PHILOS locking plate system with either delto-pectoral or trans-deltoid approach and they are followed up at regular intervals to assess them clinicoradiologicallly and functionally by Neer’s criteria. Results: In our study we found maximum incidence of these fracture between age group of 40-80 years (66.66%) with male to female ratio of 2:1 with 19 patients having left sided and 11 patients having right sided proximal humerus fracture. Complications were found in 11 patients (36.67%). Functional evaluation was carried out using Neer’s criteria at final follow up which came to excellent results in 3, satisfactory in 18, unsatisfactory in 7 and failure in 2 patients. Average time of fracture union was 12.62 weeks. Conclusions: PHILOS locking plate system serves good purpose in management of fractures of proximal humerus but requires trained faculty to do this operation who has detailed knowledge about shoulder anatomy and mechanism of injury to reduce complications associated with this type of modality.